Prevalence and Determinants of COVID-19 Vaccine Acceptance Among Healthcare Workers: A Systematic Review - Belay Desye; Belay Desye (Frontiers Media S.A., 2022)
COVID-19 is a major public health problem that has been seriously affecting the global community. Healthcare workers (HCWs) are at high risk of infection due to being directly involved in diagnosing and taking care of patients. Due to this, they were prioritized to receive the initial supply of vaccines. However, vaccine hesitancy has been identified as a major global public health threat. Therefore, this review aimed to synthesize pieces of evidence on the prevalence of COVID-19 vaccine acceptance and determinate factors among HCWs. A systematic search of published articles was identified using PubMed, Science Direct, Web of Science, and Google Scholar for relevant studies of vaccine acceptance and determinant factors among HCWs. Published articles were identified using abstracts and titles of the articles, and articles were assessed for eligibility criteria. The review process was conducted according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). An electronic database search identified 365 articles, from which 33 full-text articles were included in the systematic review. In this review, the highest rate of vaccine acceptance was reported at 95% and the lowest rate of vaccine acceptance was found at 21%. Factors such as sex (male), age, profession (medical doctors), and previous influenza vaccination were the main positive predictors for COVID-19 vaccine acceptance among HCWs. Concerns about vaccine safety, efficacy, and effectiveness were the main barriers and drivers for vaccine hesitancy. Therefore, to improve the COVID-19 vaccine acceptance among HCWs, governments, public health authorities, and private healthcare systems should work together to provide continuous professional development and training on the safety and effectiveness of the COVID-19 vaccine.